Hollow resin particles for use in resin composition for semiconductor members

Hollow resin particles with optimized structural and compositional features address the mechanical weakness of conventional particles, providing enhanced low dielectric properties and durability for semiconductor components.

JP7618439B2Active Publication Date: 2025-01-21SEKISUI PLASTICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020209334
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-17
Publication Date
2025-01-21
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

Conventional hollow porous resin particles used in semiconductor components lack sufficient mechanical strength, leading to deformation and damage under external forces, which compromises their ability to achieve low dielectric properties.

Method used

Hollow resin particles with specific structural and compositional characteristics, including a reduction rate of dielectric constant and loss tangent, a volume average particle diameter, and a porous or single hollow structure, are developed to enhance mechanical strength and maintain low dielectric properties.

Benefits of technology

The developed hollow resin particles exhibit excellent low dielectric properties and mechanical durability, ensuring reliable performance in semiconductor components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618439000007
    Figure 0007618439000007
  • Figure 0007618439000008
    Figure 0007618439000008
  • Figure 0007618439000009
    Figure 0007618439000009
Patent Text Reader

Abstract

To provide hollow resin particles used in a resin composition for a semiconductor member which can exhibit excellent low dielectric characteristics by used in a resin composition for a semiconductor member.SOLUTION: Hollow resin particles used in a resin composition for a semiconductor member are hollow resin particles having a hole part inside the particles, in which a reduction ratio of a relative dielectric constant Dk1 of a film (F1) obtained by blending 80 pts.wt. of polyimide and 20 pts.wt. of the hollow resin particles to a relative dielectric constant Dk0 of a film (F0) composed of only the polyimide is 3% or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to hollow resin particles for use in a resin composition for a semiconductor member. [Background technology]

[0002] In recent years, with the increase in the amount of information processed and the communication speed of various electronic devices, mounting technologies such as higher integration of mounted semiconductor devices, higher density wiring, and multi-layering are rapidly progressing. Insulating resin materials used in semiconductor members used in semiconductor devices are required to have low relative dielectric constants and dielectric loss tangents in order to increase the transmission speed of high-frequency signals and reduce loss during signal transmission.

[0003] In response to such demands, a technology has been reported in which hollow particles, each of which has a shell portion and a hollow portion surrounded by the shell portion, are mixed into the insulating resin to introduce air space into the insulating resin, thereby lowering the relative dielectric constant and dielectric loss tangent.

[0004] As such a technique, for example, a technique related to hollow porous resin particles consisting of a mesoporous structure and an outer shell formed on the surface thereof has been reported (Patent Document 1). The hollow porous resin particles are obtained by simultaneously reacting an oil-soluble polymerization initiator and a water-soluble polymerization initiator when a polymerizable monomer is suspension polymerized in an aqueous system.

[0005] However, the hollow porous resin particles produced by the method described in Patent Document 1 have an extremely thin and brittle surface layer, so there is a high risk that the particles will be destroyed when an external force is applied.

[0006] As described above, conventional hollow porous resin particles do not have sufficient mechanical strength, and are prone to deformation and destruction when an external force is applied, making it difficult to maintain their shape under the application of an external force. When hollow porous resin particles having insufficient mechanical strength are applied to a resin composition used for semiconductor members such as semiconductor packages and semiconductor modules, they are destroyed by external forces during the manufacture of the semiconductor members or semiconductor devices having the semiconductor members, resulting in a problem that it is not possible to achieve a low specific dielectric constant and a low dielectric loss tangent. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-82152 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide hollow resin particles for use in a resin composition for a semiconductor member, which can provide a semiconductor member that can exhibit excellent low dielectric properties by using the resin composition for a semiconductor member. [Means for solving the problem]

[0009] The hollow resin particles used in the resin composition for semiconductor members according to an embodiment of the present invention are A hollow resin particle having a void inside the particle, The reduction rate of the dielectric constant Dk1 of a film (F1) containing 80 parts by weight of polyimide and 20 parts by weight of the hollow resin particles relative to the dielectric constant Dk0 of a film (F0) consisting only of the polyimide is 3% or more.

[0010] In one embodiment, the reduction rate of the dielectric loss tangent Df1 of the film (F1) relative to the dielectric loss tangent Df0 of the film (F0) is 3% or more.

[0011] In one embodiment, the hollow resin particles have a volume average particle size of 0.5 μm to 100 μm.

[0012] In one embodiment, the hollow resin particles contain a polymer (P) including at least one selected from the group consisting of a structural unit (I) derived from a vinyl monomer and a structural unit (II) derived from a phosphate ester monomer.

[0013] In one embodiment, the structural unit (II) derived from a phosphate ester monomer has an ethylenically unsaturated group.

[0014] In one embodiment, the phosphate ester monomer is represented by general formula (1). [ka] (In general formula (1), R 1 is a (meth)acrylic group or an allyl group, R 2 is a linear or branched alkylene group, m is an integer of 1 to 30, n is 0 or 1, v is an integer of 1 to 10, and x is 1 or 2.

[0015] In one embodiment, the hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention have a specific surface area of ​​1 m 2 / g~30m 2 / g.

[0016] In one embodiment, the hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention have a bulk density of 0.01 g / cm 3 ~0.6g / cm 3 It is.

[0017] In one embodiment, the particle has a pore structure.

[0018] In one embodiment, the particle has a hollow structure.

[0019] The semiconductor member according to the embodiment of the present invention contains hollow resin particles used in the resin composition for a semiconductor member according to the embodiment of the present invention. Effect of the Invention

[0020] According to an embodiment of the present invention, it is possible to provide hollow resin particles for use in a resin composition for a semiconductor member, which can provide a semiconductor member that can exhibit excellent low dielectric properties by using the resin composition for a semiconductor member. [Brief description of the drawings]

[0021] [Figure 1] 1 is a SEM image of the surface of resin particles (1) obtained in Example 1. [Diagram 2] 1 is a cross-sectional SEM image of resin particle (1) obtained in Example 1. [Diagram 3] 1 is a SEM image of the surface of resin particles (9) obtained in Example 9. [Figure 4] 1 is a cross-sectional SEM image of resin particle (9) obtained in Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0023] In this specification, the term "semiconductor member" refers to a member that constitutes a semiconductor, such as a semiconductor package or a semiconductor module. In this specification, the term "resin composition for semiconductor members" refers to a resin composition used for semiconductor members. Therefore, the hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention are used in the resin composition for semiconductor members, and are therefore suitable for use in semiconductor members such as semiconductor packages and semiconductor modules. Such a semiconductor member is a semiconductor member according to the embodiment of the present invention, and includes hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention.

[0024] A semiconductor package is constructed using an IC chip as an essential component and at least one member selected from molding resin, underfill material, mold underfill material, die bond material, prepreg for semiconductor package substrate, metal-clad laminate for semiconductor package substrate, and build-up material for printed circuit board for semiconductor package.

[0025] A semiconductor module is constructed using a semiconductor package as an essential component and at least one member selected from a prepreg for printed circuit boards, a metal-clad laminate for printed circuit boards, a build-up material for printed circuit boards, a solder resist material, a coverlay film, an electromagnetic shielding film, and an adhesive sheet for printed circuit boards.

[0026] In this specification, the term "(meth)acrylic" means "acrylic and / or methacrylic", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein". In this specification, the term "acid (salt)" means "acid and / or its salt". Examples of salts include alkali metal salts and alkaline earth metal salts, and specific examples include sodium salts and potassium salts.

[0027] <<Hollow resin particles>> The hollow resin particles according to the embodiment of the present invention are used in a resin composition for a semiconductor member. As described above, the resin composition for a semiconductor member is a resin composition used for a semiconductor member. Such a resin composition typically contains an insulating resin. As such an insulating resin, any appropriate resin may be adopted as long as it does not impair the effects of the present invention. Examples of such insulating resins include polyphenylene ether, polyphenylene sulfide, polyimide, polyetherimide, polybismaleimide, polyarylate, epoxy resin, polyester resin, urethane resin, acrylic resin, cyanate resin, phenol resin, polystyrene resin, fluororesin such as PTFE, and cycloolefin resin.

[0028] The hollow resin particles used in the resin composition for semiconductor members according to an embodiment of the present invention are hollow resin particles having voids inside the particles. Any appropriate structure may be adopted as the structure of the voids inside the particles as long as the effects of the present invention are not impaired. Examples of such structures that can further demonstrate the effects of the present invention include a porous structure and a single hollow structure. The voids referred to here mean a state in which the inside is filled with a substance other than resin, such as a gas or liquid, and preferably mean a state filled with gas, in terms of further demonstrating the effects of the present invention.

[0029] The volume average particle diameter of the hollow resin particles is preferably 0.5 μm to 100 μm, more preferably 1.0 μm to 80 μm, even more preferably 1.5 μm to 60 μm, and particularly preferably 2.0 μm to 40 μm. When the volume average particle diameter of the hollow resin particles is within the above range, the effect of the present invention can be more effectively exhibited. When the volume average particle diameter of the hollow resin particles is too small outside the above range, the thickness of the surface layer of the particles becomes relatively thin, and the hollow resin particles may not have sufficient mechanical strength. When the volume average particle diameter of the hollow resin particles is too large outside the above range, phase separation between the polymer and the solvent produced by polymerization of the monomer component during suspension polymerization may be difficult to occur, which may make it difficult to form the surface layer. The volume average particle diameter of the hollow resin particles can be obtained by the Coulter method described later.

[0030] The hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention have a reduction rate of the dielectric constant Dk1 of a film (F1) containing 80 parts by weight of polyimide and 20 parts by weight of the hollow resin particles relative to the dielectric constant Dk0 of a film (F0) consisting only of the polyimide, which is preferably 3% or more, more preferably 5% or more, even more preferably 10% or more, and particularly preferably 15% or more. The reduction rate of the dielectric constant Dk1 of the film (F1) relative to the dielectric constant Dk0 of the film (F0) is the higher the better, but in reality, it is 35% or less. If the reduction rate of the dielectric constant Dk1 of the film (F1) relative to the dielectric constant Dk0 of the film (F0) is within the above range, the effects of the present invention can be more effectively exhibited. If the reduction rate of the dielectric constant Dk1 of the film (F1) relative to the dielectric constant Dk0 of the film (F0) is too small outside the above range, the hollow resin particles used in the resin composition for semiconductor members according to an embodiment of the present invention may not exhibit excellent low dielectric properties.

[0031] The reduction rate of the relative dielectric constant Dk1 of the film (F1) relative to the relative dielectric constant Dk0 of the film (F0) is calculated by the following formula. Reduction rate (%) of the dielectric constant Dk1 of film (F1) relative to the dielectric constant Dk0 of film (F0) = [(Dk0-Dk1) / Dk0] x 100

[0032] The hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention have a reduction rate of the dielectric loss tangent Df1 of the film (F1) relative to the dielectric loss tangent Df0 of the film (F0) of preferably 3% or more, more preferably 5% or more, even more preferably 10% or more, and particularly preferably 15% or more. The reduction rate of the dielectric loss tangent Df1 of the film (F1) relative to the dielectric loss tangent Df0 of the film (F0) is the higher the better, but in reality, it is 35% or less. If the reduction rate of the dielectric loss tangent Df1 of the film (F1) relative to the dielectric loss tangent Df0 of the film (F0) is within the above range, the effects of the present invention can be more effectively exhibited. If the reduction rate of the dielectric loss tangent Df1 of the film (F1) relative to the dielectric loss tangent Df0 of the film (F0) is too small outside the above range, the hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention may not be able to exhibit excellent low dielectric properties.

[0033] The reduction rate of the dielectric loss tangent Df1 of the film (F1) relative to the dielectric loss tangent Df0 of the film (F0) is calculated by the following formula. Reduction rate (%) of the dielectric tangent Df1 of film (F1) relative to the dielectric tangent Df0 of film (F0) = [(Df0-Df1) / Df0] x 100

[0034] The hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention preferably have a specific surface area of ​​1 m 2 / g~30m 2 / g, more preferably 1m 2 / g~25m 2 / g, and more preferably 1m 2 / g~20m 2 / g, and particularly preferably 1m 2 / g~15m 2 / g. If the specific surface area is within the above range, the effects of the present invention can be more effectively achieved. If the specific surface area is too small outside the above range, voids are likely to form at the interface between the particles and the insulating resin, which may reduce the strength of the insulating resin material or deteriorate the low moisture absorption properties. If the specific surface area is too large outside the above range, the strength of the hollow resin particles may decrease, and the particles may be destroyed during the manufacturing process, making it impossible to maintain the hollow portion.

[0035] The hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention preferably have a bulk density of 0.01 g / cm 3 ~0.6g / cm 3 and more preferably 0.02 g / cm 3 ~0.55g / cm 3 and more preferably 0.03 g / cm 3 ~0.5g / cm 3 and particularly preferably 0.05 g / cm 3 ~0.45g / cm 3 If the bulk density is too small outside the above range, the strength of the hollow resin particles may decrease, and the particles may be broken during the manufacturing process, making it difficult to maintain the hollow space. If the bulk density is too large outside the above range, the hollow space may be reduced, making it difficult to achieve sufficient low dielectric properties.

[0036] The hollow resin particles used in the resin composition for semiconductor members according to an embodiment of the present invention preferably contain a polymer (P) containing at least one selected from the group consisting of a structural unit (I) derived from a vinyl monomer and a structural unit (II) derived from a phosphate ester monomer.

[0037] Typically, the hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention are mainly composed of a polymer (P) containing at least one selected from the group consisting of a vinyl monomer-derived structural unit (I) and a phosphate ester monomer-derived structural unit (II). Here, the term "main component" means that the content in the whole is preferably 50% by weight or more, more preferably 70% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably 98% by weight or more.

[0038] The content of the polymer (P) in the hollow resin particles used in the resin composition for semiconductor members according to an embodiment of the present invention is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably 98% by weight to 100% by weight.

[0039] The polymer (P) is preferably a polymer containing both a constituent unit (I) derived from a vinyl monomer and a constituent unit (II) derived from a phosphate ester monomer.

[0040] In this specification, all the monomer components used to produce the polymer (P) may be referred to as a monomer composition.

[0041] The vinyl monomer-derived structural unit (I) is a structural unit formed when the vinyl monomer is polymerized as one of all monomer components used to produce the polymer (P). As such a vinyl monomer, any suitable vinyl monomer may be adopted as long as it does not impair the effects of the present invention. The vinyl monomer may be one type only, or two or more types.

[0042] Examples of the vinyl monomer include a monofunctional vinyl monomer having one ethylenically unsaturated group, and a polyfunctional vinyl monomer having two or more ethylenically unsaturated groups.

[0043] Examples of monofunctional vinyl monomers having one ethylenically unsaturated group include styrene monomers, carboxyl group-containing monomers, (meth)acrylic acid alkyl esters, hydroxyl group-containing monomers, nitrogen atom-containing monomers, epoxy group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, (meth)acrylic acid alkoxyalkyl esters, (meth)acrylic acid esters having an aromatic hydrocarbon group, vinyl esters, aromatic vinyl compounds, olefins, vinyl ethers, and vinyl chloride.

[0044] Examples of styrene-based monomers include styrene, ethylvinylbenzene, α-methylstyrene, vinyltoluene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, vinylbiphenyl, and vinylnaphthalene.

[0045] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and acid anhydrides thereof (for example, maleic anhydride and itaconic anhydride).

[0046] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and isononyl (meth)acrylate. Examples of the (meth)acrylic acid alkyl ester include alkyl esters having an alkyl group having 1 to 20 carbon atoms, such as decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. The alkyl group here includes an alicyclic hydrocarbon group and an alkyl group having an alicyclic hydrocarbon group. In terms of excellent stability of the dispersion during suspension polymerization and easy production of hollow resin particles having high mechanical strength, the alkyl group is preferably an alkyl group having 1 to 8 carbon atoms, and more preferably an alkyl group having 1 to 4 carbon atoms.

[0047] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing (meth)acrylic acid esters, vinyl alcohol, and allyl alcohol. Examples of the hydroxyl group-containing (meth)acrylic acid esters include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and 4-hydroxymethylcyclohexyl (meth)acrylate.

[0048] Nitrogen atom-containing monomer is a monomer having at least one nitrogen atom in the molecule. In this specification, a monomer having both a hydroxyl group and a nitrogen atom in the molecule is not included in the hydroxyl group-containing monomer, but is included in the nitrogen atom-containing monomer. Examples of the nitrogen atom-containing monomer include N-vinyl cyclic amide, (meth)acrylamide, amino group-containing monomer, cyano group-containing monomer, heterocycle-containing monomer, imide group-containing monomer, and isocyanate group-containing monomer.

[0049] N-vinyl cyclic amides include, for example, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione.

[0050] Examples of (meth)acrylamides include (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide, N-hydroxyalkyl(meth)acrylamide, and N-alkoxyalkyl(meth)acrylamide.

[0051] Examples of N-alkyl(meth)acrylamides include N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, and N-octyl(meth)acrylamide. Examples of N-alkyl(meth)acrylamides include (meth)acrylamides having an amino group, such as dimethylaminoethyl(meth)acrylamide, diethylaminoethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide.

[0052] Examples of N,N-dialkyl(meth)acrylamides include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide.

[0053] Examples of N-hydroxyalkyl(meth)acrylamides include N-methylol(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide, and N-methyl-N-2-hydroxyethyl(meth)acrylamide.

[0054] Examples of N-alkoxyalkyl(meth)acrylamides include N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide.

[0055] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate.

[0056] Examples of cyano group-containing monomers include acrylonitrile and methacrylonitrile.

[0057] Examples of heterocycle-containing monomers include (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisoxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, and N-methylvinylpyrrolidone.

[0058] Examples of imide group-containing monomers include maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-laurylitaconimide, and N-cyclohexylitaconimide; and succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide.

[0059] An example of an isocyanate group-containing monomer is 2-(meth)acryloyloxyethyl isocyanate.

[0060] Examples of epoxy group-containing monomers include glycidyl (meth)acrylate and methylglycidyl (meth)acrylate.

[0061] An example of the sulfonic acid group-containing monomer is sodium vinyl sulfonate.

[0062] Examples of alkoxyalkyl (meth)acrylates include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate.

[0063] Examples of the (meth)acrylic acid ester having an aromatic hydrocarbon group include phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate.

[0064] Examples of vinyl esters include vinyl acetate and vinyl propionate.

[0065] Examples of the aromatic vinyl compound include styrene and vinyltoluene.

[0066] Examples of olefins include ethylene, butadiene, isoprene, and isobutylene.

[0067] Examples of vinyl ethers include vinyl alkyl ethers.

[0068] Examples of polyfunctional vinyl monomers having two or more ethylenically unsaturated groups include polyfunctional (meth)acrylic acid ester monomers and aromatic divinyl monomers.

[0069] Examples of polyfunctional (meth)acrylic acid ester monomers include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, tetradecaethylene glycol di(meth)acrylate, decaethylene glycol di(meth)acrylate, pentadecaethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, and 1,4-butaethylene glycol di(meth)acrylate. Examples of suitable acrylates include hexanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, diethylene glycol phthalate di(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, polyester (meth)acrylate, and urethane (meth)acrylate.

[0070] Examples of aromatic divinyl monomers include divinylbenzene, divinylnaphthalene, and derivatives thereof.

[0071] In order to more effectively demonstrate the effects of the present invention, it is preferable that the vinyl monomer contains a polyfunctional vinyl monomer. In order to more effectively demonstrate the effects of the present invention, the content of the polyfunctional vinyl monomer in the total amount of vinyl monomers is preferably 3% by weight to 70% by weight, more preferably 5% by weight to 50% by weight, even more preferably 7% by weight to 45% by weight, and particularly preferably 10% by weight to 40% by weight. If the content of the polyfunctional vinyl monomer in the total amount of vinyl monomers is too small outside the above range, it may be difficult to form pores inside the particles. If the content of the polyfunctional vinyl monomer in the total amount of vinyl monomers is too large outside the above range, the surface shrinkage of the obtained hollow resin particles may increase, and the mechanical strength may be weakened.

[0072] The constitutional unit (II) derived from a phosphate monomer is a constitutional unit formed when a phosphate monomer is polymerized as one of all monomer components used to produce the polymer (P). As such a phosphate monomer, any appropriate phosphate monomer can be adopted as long as it does not impair the effects of the present invention. The phosphate monomer may be one type or two or more types.

[0073] The phosphate monomer preferably has an ethylenically unsaturated group, since this monomer is copolymerized with a vinyl monomer in the vicinity of the droplet surface during suspension polymerization, thereby increasing the particle hardness.

[0074] As the phosphate monomer, an acidic phosphate monomer is preferred, since it is easily oriented on the droplet surface during suspension polymerization and can act with an inorganic dispersant to increase the hardness in the vicinity of the particle surface.

[0075] As the acidic phosphate monomer having an ethylenically unsaturated group, a phosphate monomer represented by the general formula (1) is preferred in that it can further exert the effects of the present invention. [ka]

[0076] In general formula (1), R 1 is a (meth)acrylic group or an allyl group, R 2 is a linear or branched alkylene group, m is an integer of 1 to 30, n is 0 or 1, v is an integer of 1 to 10, and x is 1 or 2.

[0077] In terms of being able to more effectively exert the effects of the present invention, the phosphate ester monomer represented by general formula (1) is preferably a caprolactone EO-modified phosphate dimethacrylate represented by formula (2), a polyoxypropylene allyl ether phosphate ester represented by formula (3), or 2-methacryloyloxyethyl acid phosphate.

[0078] [ka]

[0079] In formula (2), a and b are a=1 and b=2, or a=2 and b=1.

[0080] [ka]

[0081] In formula (3), p is an integer of 1 to 30. q is 1 or 2.

[0082] The caprolactone EO-modified phosphate dimethacrylate represented by formula (2) is available, for example, from Nippon Kayaku Co., Ltd. under the trade name "KAYAMER PM-21."

[0083] The polyoxypropylene allyl ether phosphate represented by formula (3) is available, for example, from ADEKA Corporation under the trade name "ADEKA REASOAP PP-70."

[0084] In the hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention, when the polymer (P) which is the main component is a polymer containing both the constituent unit (I) derived from a vinyl monomer and the constituent unit (II) derived from a phosphoric acid ester monomer, the content of the phosphoric acid ester monomer in the total monomer components used to produce the polymer is preferably 0.001 to 5 parts by weight, more preferably 0.01 to 3 parts by weight, even more preferably 0.03 to 1 part by weight, and particularly preferably 0.05 to 0.8 parts by weight, relative to 100 parts by weight of the vinyl monomer. If the content of the phosphoric acid ester monomer is within the above range relative to 100 parts by weight of the vinyl monomer, the effects of the present invention can be more effectively exhibited.

[0085] The hollow resin particles used in the resin composition for semiconductor members according to the embodiment of the present invention may contain any other appropriate components in addition to the polymer (P) containing at least one selected from the group consisting of the vinyl monomer-derived structural unit (I) and the phosphate ester-derived structural unit (II) as long as the effects of the present invention are not impaired. Such other components may be one type only or two or more types. Examples of such other components include pigments, antioxidants, fragrances, UV protection agents, surfactants, preservatives, and medicinal components.

[0086] <<Method for producing hollow resin particles>> The hollow resin particles used in the resin composition for a semiconductor member according to an embodiment of the present invention can be produced by any appropriate method as long as the effects of the present invention are not impaired.

[0087] Such a production method includes, for example, a dispersion step (step 1), a polymerization step (step 2), a washing step (step 3), and a drying step (step 4).

[0088] ≪Process 1: Dispersion process≫ Step 1 is a step of dispersing an organic mixed solution containing a monomer composition including at least one monomer selected from the group consisting of vinyl monomers and phosphate ester monomers, a polymerization initiator, and a non-polymerizable organic compound in an aqueous solution containing a dispersant.

[0089] The organic mixed solution may be dispersed in the aqueous solution by any suitable method as long as the organic mixed solution can be present in the aqueous solution in the form of droplets. A representative example of such a dispersion method is a dispersion method using a homomixer or a homogenizer.

[0090] The aqueous solution comprises an aqueous medium and a dispersant.

[0091] Examples of the aqueous medium include water, a mixed medium of water and a lower alcohol (methanol, ethanol, etc.), etc. The water is preferably at least one selected from deionized water, ion-exchanged water, and distilled water.

[0092] As the dispersant, any suitable dispersant may be used as long as it does not impair the effects of the present invention. Examples of such dispersants include inorganic dispersants and surfactants. In order to further develop the effects of the present invention, it is preferable to use an inorganic dispersant as the dispersant. The dispersant may be one type or two or more types.

[0093] Examples of inorganic dispersants include salts that are poorly soluble in water, such as alkaline earth metal pyrophosphates (e.g., magnesium pyrophosphate), alkaline earth metal phosphates (e.g., tricalcium phosphate), calcium carbonate, and barium carbonate; inorganic dispersants, such as silica and zirconium oxide; and inorganic polymeric substances, such as talc, bentonite, silicic acid, diatomaceous earth, and clay. The alkaline earth metals referred to here are preferably magnesium and calcium. Among these, alkaline earth metal pyrophosphates and alkaline earth metal phosphates are preferred in that metal ions interact with the phosphate moiety in the phosphate monomer to form a dense coating on the surface, thereby enabling hollow resin particles with high mechanical strength to be obtained.

[0094] The amount of inorganic dispersant added is preferably 0.1 to 30 parts by weight, and more preferably 0.5 to 20 parts by weight, per 100 parts by weight of the monomer composition (all monomer components used to produce the polymer (P), which is the main component of the hollow resin particles), in order to ensure the stability of the oil droplets and to obtain hollow resin particles with a uniform particle size.

[0095] Examples of the surfactant include anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.

[0096] Examples of the anionic surfactant include non-reactive anionic surfactants such as alkyl sulfate fatty acid salts, alkylbenzenesulfonates, alkylnaphthalenesulfonates, alkanesulfonates, alkyldiphenylethersulfonates, dialkylsulfosuccinates, monoalkylsulfosuccinates, and polyoxyethylene alkylphenylether phosphates; and reactive anionic surfactants such as polyoxyethylene-1-(allyloxymethyl)alkylether sulfate ammonium salts, polyoxyethylene alkylpropenylphenylether sulfate ammonium salts, and polyoxyalkylene alkenyl ether ammonium sulfate.

[0097] Examples of the cationic surfactant include alkyltrimethylammonium salts, alkyltriethylammonium salts, dialkyldimethylammonium salts, dialkyldiethylammonium salts, and N-polyoxyalkylene-N,N,N-trialkylammonium salts.

[0098] Examples of the zwitterionic surfactant include lauryl dimethylamine oxide, phosphate salts, and phosphite surfactants.

[0099] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polysorbitan fatty acid esters, polyoxyethylene alkylamines, glycerin fatty acid esters, and oxyethylene-oxypropylene block polymers.

[0100] The amount of the surfactant added is preferably 0.01 part by weight to 1 part by weight with respect to 100 parts by weight of the organic mixed solution. The surfactant may be one type only, or two or more types may be used.

[0101] The aqueous solution may contain any appropriate other components as long as the effects of the present invention are not impaired.

[0102] The organic mixed solution contains a monomer composition including at least one monomer selected from the group consisting of vinyl monomers and phosphate ester monomers, a polymerization initiator, and a non-polymerizable organic compound.

[0103] As for the monomer composition contained in the organic mixed solution, the explanation in the section <<Hollow Resin Particles>> can be directly applied.

[0104] As the polymerization initiator, any appropriate polymerization initiator can be used as long as it does not impair the effects of the present invention.

[0105] The polymerization initiator preferably has a 10-hour half-life temperature of 90° C. or less. Use of such a polymerization initiator can completely decompose the polymerization initiator remaining in the hollow resin particles, and can suppress oxidative deterioration of the resin and gas generation caused by the remaining polymerization initiator when, for example, a semiconductor member containing the hollow resin particles is heated by solder reflow or the like.

[0106] The polymerization initiator is preferably polymerized at a combination of reaction temperature and reaction time such that the decomposition rate of the polymerization initiator calculated by the following formula is 98% or more. By setting such polymerization conditions, the polymerization initiator remaining in the hollow resin particles can be completely decomposed, and for example, when a semiconductor member containing the hollow resin particles is heated by solder reflow or the like, oxidation degradation of the resin and gas generation due to the remaining polymerization initiator can be suppressed.

[0107] Decomposition rate (%)=(1-exp(-k d t))×100 kd = Aexp(-ΔE / RT)

[0108] In the above formula, k d represents the thermal decomposition rate constant, t represents the reaction time (hr), and A represents the frequency factor (hr -1 ), ΔE is the activation energy (J / mol), R is the gas constant (8.314 J / mol K), and T is the reaction temperature (K).

[0109] Examples of the polymerization initiator include organic peroxides such as lauroyl peroxide, benzoyl peroxide, orthochlorobenzoyl peroxide, orthomethoxybenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-ethylhexanoate, and di-t-butyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, 1,1'-azobiscyclohexanecarbonitrile, and 2,2'-azobis(2,4-dimethylvaleronitrile).

[0110] The amount of the polymerization initiator added is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, and even more preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the monomer composition (all monomer components used to produce the polymer (P) which is the main component of the hollow resin particles). The polymerization initiator may be of one kind or two or more kinds.

[0111] The non-polymerizable organic compound functions as a so-called solvent, and also contributes to the formation of pores having a porous structure or a single hollow structure inside the hollow resin particles.

[0112] As such a non-polymerizable organic compound, it is preferable to use an organic solvent having a boiling point of 30° C. or more and 200° C. or less, because it exists as a liquid in the temperature range in which the polymerization step (step 2) is carried out. More specifically, as the non-polymerizable organic compound, one or more compounds selected from the group consisting of saturated aliphatic hydrocarbons such as n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, etc., aromatic compounds such as toluene and benzene, acetate-based compounds such as ethyl acetate and butyl acetate, and fluorine-based compounds such as hydrofluoroethers and hydrofluorocarbons can be used.

[0113] The amount of the non-polymerizable organic compound used is preferably 10 to 250 parts by weight relative to 100 parts by weight of the monomer composition (all monomer components used to produce the polymer (P) which is the main component of the hollow resin particles) in order to more effectively exhibit the effects of the present invention. If the amount of the non-polymerizable organic compound used relative to 100 parts by weight of the monomer composition is too small outside the above range, there is a risk that the pores of a porous structure or a single hollow structure may not be reliably formed inside the hollow resin particles. If the amount of the non-polymerizable organic compound used relative to 100 parts by weight of the monomer composition is too large outside the above range, there is a risk that the obtained hollow resin particles may not be given sufficient strength.

[0114] The organic mixed solution may contain any other appropriate components as long as the effects of the present invention are not impaired.

[0115] ≪Step 2: Polymerization step≫ In step 2, the dispersion obtained in step 1 is heated to carry out suspension polymerization.

[0116] The polymerization temperature may be any suitable temperature suitable for suspension polymerization within a range that does not impair the effects of the present invention. Such a polymerization temperature is preferably 30°C to 105°C.

[0117] The polymerization time may be any appropriate time suitable for suspension polymerization, as long as it does not impair the effects of the present invention. Such a polymerization time is preferably 0.1 to 20 hours.

[0118] Post-heating, which is preferably carried out after polymerization, is a treatment suitable for obtaining hollow resin particles with a high degree of perfection.

[0119] The temperature of post-heating preferably carried out after polymerization may be any appropriate temperature within a range that does not impair the effects of the present invention. The temperature of such post-heating is preferably 50°C to 120°C.

[0120] The time for post-heating preferably carried out after polymerization can be any appropriate time within the range not impairing the effects of the present invention, and the time for such post-heating is preferably 1 hour to 10 hours.

[0121] <Step 3: Cleaning step> Step 3 is a step of washing the slurry obtained in step 2.

[0122] Any suitable washing method may be adopted as long as it does not impair the effects of the present invention. Examples of such washing methods include (1) a method in which after forming hollow resin particles, a high centrifugal acceleration is applied using a high-speed centrifuge or the like to precipitate the hollow resin particles, the supernatant is removed, new ion-exchanged water or distilled water is added, the precipitated hollow resin particles are dispersed in the ion-exchanged water, and this operation is repeated several times to remove impurities, (2) a method in which impurities are removed by washing using a cross-flow filtration method using a ceramic filter or the like, and (3) a method in which a solvent that acts as a particle flocculant is added to the hollow resin particles to cause the particles to flocculate and settle in the solvent, the hollow resin particles are separated using a filter or the like, and washed with a washing solvent.

[0123] In the above washing method (1), it is preferable to wash with ion-exchanged water or distilled water in an amount of at least 5 times the weight of the slurry.

[0124] For hollow resin particles having a small specific gravity, it is preferable to wash them by a cross-flow filtration method using a ceramic filter or the like (2).

[0125] ≪Step 4: Drying step≫ Step 4 is a step of drying the washed slurry obtained in step 3.

[0126] As the drying method, any appropriate drying method can be adopted as long as it does not impair the effects of the present invention. Examples of such drying methods include drying by heating.

[0127] The heating temperature may be any appropriate temperature within a range that does not impair the effects of the present invention, and is preferably 50°C to 120°C.

[0128] The heating time may be any appropriate time within the range that does not impair the effects of the present invention, and is preferably 1 hour to 50 hours. EXAMPLES

[0129] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".

[0130] <Measurement of volume average particle size> The volume average particle size of the particles was measured by the Coulter method as follows. The volume average particle size of the particles was measured using a Coulter Multisizer® 3 (a measuring device manufactured by Beckman Coulter, Inc.). The measurement was performed using an aperture calibrated according to the Multisizer® 3 user's manual published by Beckman Coulter, Inc. The aperture used in the measurement was appropriately selected depending on the size of the particles to be measured. Current (aperture current) and Gain (gain) were appropriately set depending on the size of the selected aperture. For example, when an aperture having a size of 50 μm was selected, Current (aperture current) was set to -800 and Gain (gain) was set to 4. The measurement sample was prepared by dispersing 0.1 g of particles in 10 ml of 0.1% by weight nonionic surfactant aqueous solution using a touch mixer (Yamato Scientific Co., Ltd., "TOUCHMIXER MT-31") and an ultrasonic cleaner (Velvoclear Co., Ltd., "ULTRASONIC CLEANER VS-150") to prepare a dispersion. During the measurement, the beaker was gently stirred to prevent air bubbles from being introduced, and the measurement was terminated when 100,000 particles were measured. The volume average particle size of the particles was taken as the arithmetic mean of the particle size distribution based on the volume of 100,000 particles.

[0131] <Bulk density> The bulk density of the particles was measured in accordance with JIS K5101-12-1 (Test methods for pigments - Part 12: Apparent density or apparent specific volume - Section 1: Static method).

[0132] <Specific surface area> The specific surface area of ​​the particles was measured by the BET method (nitrogen adsorption method) described in ISO 9277 1st Edition JIS Z 8830: 2001. The BET nitrogen adsorption isotherm of the target particles was measured using an automatic specific surface area / pore distribution measuring device "Tristar II" manufactured by Shimadzu Corporation, and the specific surface area was calculated from the amount of nitrogen adsorption using the BET multipoint method. After pretreatment by heated gas purging, nitrogen was used as the adsorbate, and the adsorbate cross section was 0.162 nm 2 The measurements were carried out using a constant volume method under the following conditions: Specifically, the pretreatment was carried out by purging with nitrogen for 20 minutes while heating the container containing the particles at 65°C, allowing it to cool to room temperature, and then, while heating the container at 65°C, vacuum degassing was carried out until the pressure inside the container reached 0.05 mmHg or less.

[0133] <Measurement of relative dielectric constant Dk and dielectric loss tangent Df when polyimide resin (A) is used as insulating resin> As the polyimide resin (A), polyimide KPI-MX300F (manufactured by Kawamura Sangyo Co., Ltd., relative dielectric constant Dk = 3.45 and dielectric loss tangent Df = 0.032 measured under the conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23 °C by the cavity resonance perturbation method) was used. The particles to be measured were dispersed in ethyl acetate so that the particle concentration was 20% by weight based on the total solid content (polyimide resin + particles). Defoaming and stirring were carried out using a planetary stirring defoamer (KURABO, Mazelstar KK-250) to prepare an evaluation mixture. After the evaluation mixture was coated on a glass plate with a thickness of 5 mm using an applicator set to a wet thickness of 250 μm, ethyl acetate was removed by heating at 60 °C for 30 minutes, 90 °C for 10 minutes, 150 °C for 30 minutes, and 200 °C for 30 minutes, and then cooled to room temperature to obtain film samples containing each particle. The relative dielectric constant and dielectric loss tangent of the obtained film were evaluated by the cavity resonance method (measurement frequency: 5.8 GHz).

[0134] <Measurement of relative dielectric constant Dk when using polyimide resin (B) as the insulating resin> As the polyimide resin (B), a super high heat-resistant polyimide varnish (SPIXAREA HR002, Somal Co., Ltd., relative dielectric constant Dk = 2.5 measured under the conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23 °C by the cavity resonance perturbation method) was used. The particles to be measured were dispersed in N-methyl-2-pyrrolidone so that the particle concentration was 20% by weight based on the total solid content (polyimide resin + particles). Defoaming and stirring were carried out using a planetary stirring defoamer (KURABO, Mazelstar KK-250) to prepare an evaluation mixture. After the evaluation mixture was coated on a glass plate with a thickness of 5 mm using an applicator set to a wet thickness of 250 μm, the solvent was removed by heating at 120 °C for 10 minutes, 180 °C for 180 minutes, and 270 °C for 60 minutes, and then cooled to room temperature to obtain film samples containing each particle. The relative dielectric constant of the obtained film was evaluated by the cavity resonance method (measurement frequency: 5.8 GHz).

[0135] <SEM observation> The particles were imaged with a scanning electron microscope (SEM) to obtain surface SEM images, and then the particles were embedded in epoxy resin, cut into thin slices, and the cross sections of the particles were imaged with a scanning electron microscope (SEM) to obtain cross-sectional SEM images.

[0136] Example 1 105 parts by weight of methyl methacrylate (MMA), 45 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 0.3 parts by weight of "KAYAMER (registered trademark) PM-21" (manufactured by Nippon Kayaku Co., Ltd.) as a polymerizable monomer having an acidic phosphate ester group, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Nippon Finechem Co., Ltd., product name "ABN-V", 10-hour half-life temperature = 51 °C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 10 18 hr -1 An oil phase was prepared by mixing 0.75 parts by weight of ethyl acetate as a non-polymerizable organic compound and 75 parts by weight of cyclohexane. Also, 900 parts by weight of deionized water as an aqueous medium and 23 parts by weight of magnesium pyrophosphate produced by a double decomposition method as a dispersant were mixed together to prepare an aqueous phase. Next, the oil phase was dispersed in the water phase using a TK-Homomixer (manufactured by Primix) at 8000 rpm for 5 minutes to obtain a dispersion having a volume average particle size of approximately 8 μm. The dispersion was then placed in a polymerization vessel equipped with a stirrer and a thermometer, and the internal temperature of the polymerization vessel was raised to 55° C. and the suspension was stirred for 5 hours. The internal temperature of the polymerization vessel was then raised to 70° C. (secondary temperature increase), and the suspension was stirred at 70° C. for 7 hours (ABN-V decomposition rate=99.57%) to complete the suspension polymerization reaction. After cooling the suspension, the dispersant (magnesium pyrophosphate) contained in the suspension was decomposed with hydrochloric acid. The suspension was then dehydrated by filtration using a centrifugal filter to separate the solids, and the solids were washed with sufficient ion-exchanged water. The solids were then vacuum-dried at 70°C for 24 hours to remove non-polymerizable organic compounds, and spherical resin particles (1) were obtained. The volume average particle diameter of the resin particles (1) was 7.8 μm. According to SEM observation, the resin particles (1) had a porous shape inside. The bulk density of the resin particles (1) was 0.33 g / cm 3 It was. The specific surface area of ​​the resin particles (1) was measured before and after treatment with a jet mill at a pressure of 0.4 MPa, and was found to be 8.2 m 2 / g, 23.2m 2 This indicates that the smaller the difference in the specific surface area before and after the jet mill, the more durable the particles are against the impact of the jet mill, which means that the particles are not destroyed by external forces such as shear force and pressure during the production of semiconductor parts. In addition, the relative dielectric constant Dk and the dielectric loss tangent Df were measured. The results are shown in Table 1. A surface SEM image of resin particle (1) is shown in Figure 1. A cross-sectional SEM image of resin particle (1) is shown in Figure 2. It was confirmed that in resin particle (1) produced using an alkyl (meth)acrylate ester and a polyfunctional (meth)acrylate monomer, the particle surface was a dense shell without voids, and the inside of the particle had a porous structure.

[0137] Example 2 54 parts by weight of styrene (St), 36 parts by weight of ethylene glycol dimethacrylate (EGDMA), 0.3 parts by weight of "KAYAMER (registered trademark) PM-21" (manufactured by Nippon Kayaku Co., Ltd.) as a polymerizable monomer having an acidic phosphate ester group, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Nippon Finechem Co., Ltd., product name "ABN-V", 10-hour half-life temperature = 51 °C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 10 18 hr -1 Spherical resin particles (2) were obtained in the same manner as in Example 1, except that the oil phase was prepared by mixing 0.75 parts by weight of ethyl acetate as a non-polymerizable organic compound and 105 parts by weight of cyclohexane as a non-polymerizable organic compound. The results are shown in Table 1.

[0138] Example 3 135 parts by weight of methyl methacrylate (MMA), 15 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 0.3 parts by weight of "KAYAMER (registered trademark) PM-21" (manufactured by Nippon Kayaku Co., Ltd.) as a polymerizable monomer having an acidic phosphate ester group, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Nippon Finechem Co., Ltd., product name "ABN-V", 10-hour half-life temperature = 51 °C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 10 18 hr -1 Spherical resin particles (3) were obtained in the same manner as in Example 1, except that the oil phase was prepared by mixing 0.75 parts by weight of ethyl acetate and 75 parts by weight of cyclohexane as a non-polymerizable organic compound. The results are shown in Table 1.

[0139] Example 4 105 parts by weight of isobutyl methacrylate (IBMA), 45 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 0.3 parts by weight of "KAYAMER (registered trademark) PM-21" (manufactured by Nippon Kayaku Co., Ltd.) as a polymerizable monomer having an acidic phosphate ester group, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Nippon Finechem Co., Ltd., product name "ABN-V", 10-hour half-life temperature = 51 °C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 10 18 hr -1 Spherical resin particles (4) were obtained in the same manner as in Example 1, except that the oil phase was prepared by mixing 0.75 parts by weight of ethyl acetate and 75 parts by weight of cyclohexane as a non-polymerizable organic compound. The results are shown in Table 1.

[0140] Example 5 105 parts by weight of styrene, 45 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 0.8 parts by weight of "ADEKA REASOAP PP-70" (manufactured by ADEKA Corporation) as a polymerizable monomer having an acidic phosphate ester group, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Japan Finechem Co., Ltd., product name "ABN-V"; 10-hour half-life temperature = 51°C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 10 18 hr -1 Spherical resin particles (5) were obtained in the same manner as in Example 1, except that the oil phase was prepared by mixing 0.75 parts by weight of ethyl acetate and 75 parts by weight of cyclohexane as a non-polymerizable organic compound. The results are shown in Table 1.

[0141] Example 6 Except for changing the non-polymerizable organic compound to 150 parts by weight of cyclohexane, spherical resin particles (6) were obtained in the same manner as in Example 1. According to SEM observation, resin particles (6) were particles having only one internal hole. The results are shown in Table 1.

[0142] Example 7 In Example 1, when dispersing the prepared oil phase in the aqueous phase, the rotation speed of the TK-Homomixer was changed to 2500 rpm to obtain a dispersion liquid of approximately 35 μm. The same procedure as in Example 1 was repeated to obtain spherical resin particles (7). The results are shown in Table 1.

[0143] Example 8 Methyl methacrylate (MMA) 65 parts by weight, ethylene glycol dimethacrylate (EGDMA) 85 parts by weight, a polymerizable monomer having an acidic phosphate group "KAYAMER (registered trademark) PM-21" (manufactured by Nippon Kayaku Co., Ltd.) 0.3 parts by weight, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Nippon Finechem Co., Ltd., trade name "ABN-V", 10-hour half-life temperature = 51 °C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 10 18 hr -1An oil phase was prepared by mixing 0.75 parts by weight of ethyl acetate as a non-polymerizable organic compound and 75 parts by weight of cyclohexane as a non-polymerizable organic compound, and an aqueous phase was prepared by mixing 900 parts by weight of deionized water as an aqueous medium and 90 parts by weight of calcium phosphate tribasic as a dispersant. Other than the above, the same procedure as in Example 1 was repeated to obtain spherical resin particles (8). The volume average particle diameter of the resin particles (8) was 8.0 μm. According to SEM observation, the resin particles (8) had a porous shape inside. The bulk density of the resin particles (8) was 0.32 g / cm. 3 It was. The specific surface area of ​​the resin particles (8) was measured before and after treatment with a jet mill at a pressure of 0.4 MPa, and was found to be 7.2 m 2 / g, 10.2m 2 / g. In addition, the relative dielectric constant Dk and the dielectric loss tangent Df were measured. The results are shown in Table 1.

[0144] Example 9 Styrene (St) 63 parts by weight, divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) 102 parts by weight, HS Crysta 4100 (side chain crystalline polyolefin, manufactured by Toyokuni Oil Mills Co., Ltd.) 15 parts by weight, polymerizable monomer having an acidic phosphate ester group "KAYAMER (registered trademark) PM-21" (manufactured by Nippon Kayaku Co., Ltd.) 0.3 parts by weight, LPO (manufactured by NOF Corp., trade name "Perloil L", 10-hour half-life temperature = 61.6 °C, activation energy ΔE = 126.5 kJ / mol, frequency factor A = 3.81 × 10 18 hr -1 An oil phase was prepared by mixing 1.5 parts by weight of toluene as an aqueous medium and 120 parts by weight of heptane as a non-polymerizable organic compound. An aqueous phase was prepared by mixing 900 parts by weight of deionized water as an aqueous medium and 23 parts by weight of magnesium pyrophosphate produced by a double decomposition method as a dispersant. Next, the oil phase was dispersed in the water phase using a TK-Homomixer (manufactured by Primix) at 8000 rpm for 5 minutes to obtain a dispersion having a volume average particle size of about 8.0 μm. The dispersion was then placed in a polymerization vessel equipped with a stirrer and a thermometer, and the internal temperature of the polymerization vessel was raised to 55° C. and the suspension was stirred for 5 hours. The internal temperature of the polymerization vessel was then raised to 70° C. (secondary temperature increase), and the suspension was stirred at 80° C. for 8 hours (perloyl L decomposition rate=99.73%) to complete the suspension polymerization reaction. After cooling the suspension, the suspension was dehydrated by filtration using a centrifugal filter to separate the solid content, and the solid content was washed with sufficient ion-exchanged water. After that, the solid content was vacuum-dried at 70° C. for 24 hours to remove non-polymerizable organic compounds, and spherical resin particles (9) were obtained. The volume average particle diameter of the resin particles (9) was 8.0 μm. According to SEM observation, the resin particles (9) had a porous shape inside. The bulk density of the resin particles (9) was 0.07 g / cm. 3 It was. The specific surface area of ​​the resin particles (9) was measured before and after treatment with a jet mill at a pressure of 0.4 MPa, and was found to be 15.6 m 2 / g, 21.3m 2 / g. The dielectric constant Dk and the dielectric loss tangent Df were also measured. The results are shown in Table 1. A surface SEM image of resin particle (9) is shown in Figure 3. A cross-sectional SEM image of resin particle (9) is shown in Figure 4. It was confirmed that in resin particle (9) produced using a styrene-based monomer and an aromatic divinyl-based monomer, the particle surface was a dense shell without voids, and the inside of the particle had a porous structure.

[0145] Example 10 Styrene (St) 105 parts by weight, divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) 45 parts by weight, 2,2'-azobis(2,4-dimethylvaleronitrile) as an oil-soluble polymerization initiator (manufactured by Nippon Finechem Co., Ltd., trade name "ABN-V", 10-hour half-life temperature = 51 °C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 1018 hr -1 An oil phase was prepared by mixing 1.5 parts by weight of cyclohexane as a non-polymerizable organic compound and 150 parts by weight of cyclohexane as a non-polymerizable organic compound. An aqueous phase was prepared by mixing 900 parts by weight of deionized water as an aqueous medium, 1 part by weight of sodium lauryl sulfate as a dispersant, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name "VA-057") as a water-soluble polymerization initiator, 10-hour half-life temperature = 57 ° C, activation energy ΔE = 122.7 kJ / mol, frequency factor A = 1.80 × 1018 hr-1) 2.3 parts by weight. Next, the oil phase was dispersed in the water phase using a TK-Homomixer (manufactured by Primix) at 8000 rpm for 5 minutes to obtain a dispersion of approximately 8 μm. The dispersion was then placed in a polymerization vessel equipped with a stirrer and a thermometer, and the internal temperature of the polymerization vessel was raised to 60° C. and the suspension was stirred for 5 hours. The internal temperature of the polymerization vessel was then raised to 70° C. (secondary temperature rise), and the suspension was stirred at 70° C. for 16 hours (decomposition rate of VA-057=99.76%) to complete the suspension polymerization reaction. By ensuring sufficient reaction time of divinylbenzene, high strength can be obtained. After cooling the suspension, the suspension was dehydrated by filtration using a centrifugal filter to separate the solid content, and the solid content was washed with sufficient distilled water. After that, the solid content was vacuum dried at 70° C. for 24 hours to remove non-polymerizable organic compounds, and spherical resin particles (10) were obtained. The volume average particle diameter of the resin particles (10) was 8.1 μm. According to SEM observation, the resin particles (10) had a porous shape inside. The bulk density of the resin particles (10) was 0.30 g / cm. 3 It was. The specific surface area of ​​the resin particles (10) was measured before and after treatment with a jet mill at a pressure of 0.4 MPa, and was found to be 1.9 m 2 / g, 28.3m 2 / g. In addition, the relative dielectric constant Dk and the dielectric loss tangent Df were measured. The results are shown in Table 1.

[0146] Example 11 Styrene (St) 63 parts by weight, divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) 102 parts by weight, HS Crysta 4100 (side chain crystalline polyolefin, manufactured by Toyokuni Oil Mills Co., Ltd.) 15 parts by weight, LPO (manufactured by NOF Corp., trade name "Perloil L", 10-hour half-life temperature = 61.6 °C, activation energy ΔE = 126.5 kJ / mol, frequency factor A = 3.81 × 10) as an oil-soluble polymerization initiator 18 hr -1 An oil phase was prepared by mixing 1.65 parts by weight of ethanol as an aqueous medium and 120 parts by weight of heptane as a non-polymerizable organic compound. An aqueous phase was prepared by mixing 900 parts by weight of deionized water as an aqueous medium and 23 parts by weight of magnesium pyrophosphate produced by a double decomposition method as a dispersant. Next, the oil phase was dispersed in the water phase using a TK-Homomixer (manufactured by Primix Corporation) at 9000 rpm for 10 minutes, and the dispersion was then mixed with a Microfluidizer (HC-5000, manufactured by Mizuho Kogyo Co., Ltd.) at 100 kg / cm 2 A dispersion of about 4 μm was obtained by passing the suspension once under a pressure of 100 μm. The dispersion was then placed in a polymerization vessel equipped with a stirrer and a thermometer, and the internal temperature of the polymerization vessel was raised to 70° C. and the suspension was stirred for 10 hours. The internal temperature of the polymerization vessel was then raised to 80° C. (secondary temperature increase), and the suspension was stirred at 80° C. for 8 hours (perloyl L decomposition rate=99.73%) to complete the suspension polymerization reaction. After cooling the suspension, the suspension was dehydrated by filtration using a centrifugal filter to separate the solid content, and the solid content was washed with sufficient ion-exchanged water. After that, the solid content was vacuum-dried at 70° C. for 24 hours to remove non-polymerizable organic compounds, and spherical resin particles (11) were obtained. The volume average particle diameter of the resin particles (11) was 3.5 μm. According to SEM observation, the resin particles (11) had a porous shape inside. The bulk density of the resin particles (11) was 0.2 g / ml. The specific surface area of ​​the resin particles (11) was measured before and after treatment with a jet mill at a pressure of 0.4 MPa, and was found to be 3.8 m 2 / g, 20m 2 / g. In addition, the relative dielectric constant Dk and the dielectric loss tangent Df were measured. The results are shown in Table 1.

[0147] Example 12 Styrene (St) 63 parts by weight, divinylbenzene (DVB) 810 (manufactured by Nippon Steel Chemical & Material Co., Ltd., 81% content, 19% is ethylvinylbenzene (EVB)) 102 parts by weight, HS Crysta 4100 (side chain crystalline polyolefin, manufactured by Toyokuni Oil Mills Co., Ltd.) 15 parts by weight, LPO (manufactured by NOF Corp., trade name "Perloil L", 10-hour half-life temperature = 61.6 °C, activation energy ΔE = 126.5 kJ / mol, frequency factor A = 3.81 × 10) as an oil-soluble polymerization initiator 18 hr -1 An oil phase was prepared by mixing 1.65 parts by weight of toluene as an aqueous medium and 120 parts by weight of cyclohexane as a non-polymerizable organic compound. An aqueous phase was prepared by mixing 900 parts by weight of deionized water as an aqueous medium and 1 part by weight of sodium lauryl sulfate as a surfactant. Next, the oil phase was pre-dispersed in the water phase using "Clearmix" (M Technique Co., Ltd.) at 8000 rpm for 5 minutes, and then at 18000 rpm for 10 minutes to obtain a dispersion of approximately 1 μm. The dispersion was then placed in a polymerization vessel equipped with a stirrer and a thermometer, and the internal temperature of the polymerization vessel was raised to 70°C and the suspension was stirred for 10 hours. The internal temperature of the polymerization vessel was then raised to 80°C (secondary heating), and the suspension was stirred at 80°C for 8 hours (perloyl L decomposition rate = 99.73%) to complete the suspension polymerization reaction. After cooling the suspension, the suspension was dehydrated by filtration using a centrifugal filter to separate the solid content, and the solid content was washed with sufficient ion-exchanged water. After that, the solid content was vacuum-dried at 70° C. for 24 hours to remove non-polymerizable organic compounds, and spherical resin particles (12) were obtained. The volume average particle diameter of the resin particles (12) was 1.2 μm. According to SEM observation, the resin particles (12) had a porous shape inside. The bulk density of the resin particles (12) was 0.3 g / ml. The specific surface area of ​​the resin particles (12) was measured before and after treatment with a jet mill at a pressure of 0.4 MPa, and was found to be 5.6 m2 / g, 12.4m 2 / g. In addition, the relative dielectric constant Dk and the dielectric loss tangent Df were measured. The results are shown in Table 1.

[0148] [Table 1]

[0149] As shown in Examples 1 to 12, it was found that the hollow resin particles used in the resin composition for semiconductor components according to the embodiment of the present invention can exhibit excellent low dielectric properties. Therefore, the hollow resin particles used in the resin composition for semiconductor components according to the embodiment of the present invention can exhibit excellent low dielectric properties, and can provide a highly reliable semiconductor component. [Industrial Applicability]

[0150] The hollow resin particles used in the resin composition for a semiconductor member according to the embodiment of the present invention are used in the resin composition for a semiconductor member, and therefore can be suitably used for semiconductor members such as semiconductor packages and semiconductor modules.

Claims

1. A hollow resin particle having a void inside the particle, the hollow resin particles contain a polymer (P) containing both a structural unit (I) derived from a vinyl monomer and a structural unit (II) derived from a phosphate ester monomer, the polymer (P) is obtained by polymerizing all monomer components including a vinyl monomer and a phosphate monomer, and the content of the phosphate monomer relative to 100 parts by weight of the vinyl monomer is 0.001 parts by weight to 5 parts by weight; The reduction rate of the dielectric constant Dk1 relative to the dielectric constant Dk0 calculated from the dielectric constant Dk1 and the dielectric constant Dk0 measured by the measurement method shown below is 3% or more. Hollow resin particles for use in a resin composition for semiconductor members. However, regarding the above-mentioned relative dielectric constants Dk1 and Dk0, a polyimide having a relative dielectric constant Dk=3.45 and a dielectric loss tangent Df=0.032 measured by a cavity resonance perturbation method under conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. was used, and the hollow resin particles to be measured were dispersed in ethyl acetate so that the hollow resin particle concentration was 20% by weight relative to the total solid content (polyimide resin + hollow resin particles), and the mixture for evaluation was prepared by degassing and stirring using a planetary stirring and defoaming machine. The mixture was then applied to a glass plate having a thickness of 5 mm using an applicator set to a wet thickness of 250 μm, and then incubated at 60° C. for 30 minutes, at 90° C. for 10 minutes, and at 150° C. for 30 minutes. The ethyl acetate was removed by heating at 200°C for 30 minutes and then at 200°C for 30 minutes, and then the mixture was cooled to room temperature. The dielectric constant Dk1 of the resulting film (F1) containing 80 parts by weight of polyimide and 20 parts by weight of hollow resin particles was measured by a cavity resonance method (measurement frequency: 5.8 GHz). On the other hand, the dielectric constant Dk0 of a film (F0) consisting of only polyimide obtained in the same manner without using hollow resin particles but using polyimide having a dielectric constant Dk = 3.45 and a dielectric loss tangent Df = 0.032 measured by a cavity resonance perturbation method under conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23°C was measured by a cavity resonance perturbation method (measurement frequency: 5.8 GHz).

2. Hollow resin particles for use in the resin composition for semiconductor components described in claim 1, wherein the reduction rate of the dielectric loss tangent Df1 relative to the dielectric loss tangent Df0, calculated from the dielectric loss tangent Df1 and the dielectric loss tangent Df0 measured by the measurement method shown below, is 3% or more. However, for the dielectric loss tangent Df1 and the dielectric loss tangent Df0, a polyimide having a relative dielectric constant Dk=3.45 and a dielectric loss tangent Df=0.032 measured by a cavity resonance perturbation method under conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. was used, and the hollow resin particles to be measured were dispersed in ethyl acetate so that the hollow resin particle concentration was 20% by weight relative to the total solid content (polyimide resin + hollow resin particles), and the mixture for evaluation was prepared by degassing and stirring using a planetary stirring and defoaming machine. The mixture was then applied to a glass plate having a thickness of 5 mm using an applicator set to a wet thickness of 250 μm, and then incubated at 60° C. for 30 minutes, at 90° C. for 10 minutes, and at 150° C. for 3 minutes. The ethyl acetate was removed by heating at 200°C for 30 minutes and then at 200°C for 30 minutes, and then the mixture was cooled to room temperature. The dielectric loss tangent Df1 of the obtained film (F1) containing 80 parts by weight of polyimide and 20 parts by weight of hollow resin particles was measured by a cavity resonance method (measurement frequency: 5.8 GHz). On the other hand, the same procedure was carried out using a polyimide having a relative dielectric constant Dk = 3.45 and a dielectric loss tangent Df = 0.032 measured by a cavity resonance perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C, but without using hollow resin particles, and the dielectric loss tangent Df0 of the film (F0) consisting of only polyimide was measured by a cavity resonance method (measurement frequency: 5.8 GHz).

3. The hollow resin particles used in the resin composition for semiconductor members according to claim 1 or 2, wherein the hollow resin particles have a volume average particle diameter of 0.5 μm to 100 μm.

4. The hollow resin particle for use in a resin composition for a semiconductor member according to any one of claims 1 to 3, wherein the structural unit (II) derived from a phosphate ester monomer has an ethylenically unsaturated group.

5. The hollow resin particles for use in the resin composition for a semiconductor member according to any one of claims 1 to 4, wherein the phosphate ester-based monomer is represented by general formula (1): 【Chemistry 1】 (In general formula (1), R 1 is a (meth)acrylic group or an allyl group, R 2 is a linear or branched alkylene group, m is an integer from 1 to 30, n is 0 or 1, v is an integer from 1 to 10, and x is 1 or 2.

6. Specific surface area is 1m 2 / g to 30m 2 The hollow resin particles for use in the resin composition for a semiconductor member according to any one of claims 1 to 5, wherein the hollow resin particles have a viscosity of 1 / g.

7. Bulk density is 0.01 g / cm 3 ~0.6g / cm 3 The hollow resin particles used in the resin composition for a semiconductor member according to any one of claims 1 to 6,

8. The hollow resin particle used in the resin composition for a semiconductor member according to any one of claims 1 to 7, wherein the structure of the voids inside the particle is a porous structure.

9. The hollow resin particle used in the resin composition for a semiconductor member according to any one of claims 1 to 7, wherein the structure of the cavity inside the particle is a single hollow structure.

10. A semiconductor member comprising hollow resin particles used in the resin composition for a semiconductor member according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition for organic insulating material, organic insulating material, sealing material and circuit board

    JP2000311518A

  • Aqueous dispersion for forming low-dielectric constant insulation film, the resultant low-dielectric constant insulation film, and electronic component

    JP2001294815A

  • Porous resin particle, method for producing the same and structure

    JP2017082152A

  • Flexible metal laminate and manufacturing method thereof

    JP2017525585A

  • Hollow polymer particles and method for manufacturing same

    WO2020054816A1